Identity in action : Christian excellence in all of life - Glanzer, Perry L. (Perry Lynn) (ACU Press, 2021)
"Colleges today are filled with talk about identity and identity politics. But Glanzer shifts the conversation in Identity in Action by focusing on something one rarely hears anyone mention--the idea of identity excellence. In various professions, identity excellence means becoming an excellent accountant, biologist, historian, social worker, or teacher. But professors rarely go farther to talk the identities that really matter to students. What does it mean to be: an excellent friend? a good neighbor? a steward of one's body, possessions, or the environment? And what about social identities? How does Christianity impact: how I think about race? or gender? or citizenship? Students are often unaware of how to resolve conflicts between these identities on their own. Identity in Action, empowers readers to be excellent--and think deeply about the "why" questions of life in a practical, theologically informed manner. With personal stories and expert research, Glanzer explains how students can untangle the confusion and integrate their core identities with excellence."--